The servant of Yahweh : a critical and exegetical study of the Servant Songs in Deutero-Isaiah - Dijkman, Jan Hendrik Leonard (Rhodes University, Faculty of Divinity, Department of Divinity, 1961)
For more than two thousand years the question of tbe identity of the Servant of Yahweh in Is. 40 - 55, and especially in the so-called "Servant Songs", has exercised the minds of students of the Old Testament. The first answer which we may trace with any certainty is that of the translator of this particular section in the Septuagint, who adds the words "Jacob" and "Israel" to the text. This is closely followed in the New Testament by the answer which Philip gave to the Ethiopian eunuch's query, "Of whom speaketh the prophet this ? of himself, or of some other ?" ( Acts 8:34f,). These two answers are typical of the two possible extremes in solving the problem. The first sees the Servant as a collective entity, the people Israel, while the second sees him as an individual figure, namely, Jesus Christ. The second answer explains why the interpretation of the Servant figure has been such a live issue throughout the entire history of Christendom. In it Christians have seen a prophecy of Jesus Christ - and more particularly in the suffering of the Servant, a prophecy of the facts which form the basis of the Christian Salvation, the death and resurrection of Jesus. Until the close of the eighteenth century, the generally accepted interpretation of the figure of the Suffering Servant among Christians was to identify him completely with Christ. With the development of the scientific study of the Old Testament during the last two centuries, every generation has raised the question afresh and sought to answer it. There is hardly an Old Testament scholar who has not laboured over it, and many have published their attempts at a solution. Hence the literature on the subject is enormous. In the present study no attempt has been made to give an exhaustive survey of all the interpretations of the Servant figure, but the text of the Servant Songs has been examined before an interpretation of the Servant figure was attempted. It is to be hoped that the final interpretation here given will reflect the thought of the prophet rather than that of the interpreter.
Keywords: Bible -- Criticism, interpretation, etc.; Servant songs